2018
DOI: 10.1007/s11869-018-0618-9
|View full text |Cite
|
Sign up to set email alerts
|

Can houseplants improve indoor air quality by removing CO2 and increasing relative humidity?

Abstract: High indoor CO 2 concentrations and low relative humidity (RH) create an array of well-documented human health issues. Therefore, assessing houseplants' potential as a low-cost approach to CO 2 removal and increasing RH is important. We investigated how environmental factors such as 'dry' (< 0.20 m 3 of water per m 3 of substrate, m 3 m-3) or 'wet' (> 0.30 m 3 m-3) growing substrates, and indoor light levels ('low' 10 µmol m-2 s-1 , 'high' 50 µmol m-2 s-1 and 'very high' 300 µmol m-2 s-1), influence the plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 45 publications
7
43
1
Order By: Relevance
“…Indoor plants can act as a simple low-cost form of ventilation, reducing indoor ventilation requirements (by ~ 6%) with CO2 removal and consequently providing a reduction in building energy consumption, but only under certain environmental conditions i.e. a very high light level (~ 22000 lux) -as confirmed by several previous studies (Torpy et al, 2014;Torpy et al, 2017;Gubb et al, 2018).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Indoor plants can act as a simple low-cost form of ventilation, reducing indoor ventilation requirements (by ~ 6%) with CO2 removal and consequently providing a reduction in building energy consumption, but only under certain environmental conditions i.e. a very high light level (~ 22000 lux) -as confirmed by several previous studies (Torpy et al, 2014;Torpy et al, 2017;Gubb et al, 2018).…”
Section: Introductionmentioning
confidence: 66%
“…Several studies have shown that light levels significantly influence a plants ability to remove CO2 via their impact on stomata as a main pathway for CO2 uptake (Pennisi and van Iersel, 2012;Torpy et al, 2014;Torpy et al, 2017;Gubb et al, 2018). Indoors, the light level is typically between 0 -500 lux, but can be as high as 3000 lux in certain workplace environments (Boyce and Raynham, 2009;Lai et al, 2009;Hawkins, 2011;Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…where, Q is infiltration rate of air entering the room, V is volume of air in the office (m 3 ), t is time interval (s), C t is indoor concentration of CO 2 at time t (ppm), C ext is concentration of CO 2 in the ambient air (ppm), and C 0 is indoor CO 2 concentration at time 0 (ppm) [29,30]. The volume of air in the office (V) was calculated from the size of the room (4 m x 10 m x 3 m), Interval (t) was 3600 seconds from hourly average data, C ext was average monitoring outdoor CO 2 concentration at 430 ppm, C t was the monitored CO 2 concentration at time t (i.e., 18:00), and C 0 was the monitored CO 2 concentration at one hour before t (i.e., 17:00).…”
Section: Simple Ventilation Practices For Improving Iaqmentioning
confidence: 99%